How teachers might open dialogic spaces in writing instruction. (2016) - Jesson, Rebecca; Rosedale, Naomi
Highlights: Classroom dialogic spaces in writing lessons are analysed. Most spaces allowed particular sources of voice. Dialogic spaces were wide when texts were used for discovery. Few sites invited students' diverse textual histories. Abstract: In this article, writing lessons are examined to identify the range of ways that teachers might open dialogic space for writers. We use vignettes of teaching interactions to develop a taxonomy of the approaches that potentially make a range of voices apparent for students' consideration. Using examples from writing lessons we illustrate how these spaces are variously opened. But we also identify common barriers to including the different sources of dialogue. We identify few sites that allow inter-animation of different types of voice. We propose a practical framing for considering the ways that writing instruction might offer potential for inter-animation between texts, authors of texts and readers of texts.